Aligned N-doped carbon nanotube bundles with interconnected hierarchical structure as an efficient bi-functional oxygen electrocatalyst. Issue 46 (19th July 2018) - Tian, Weiliang; Wang, Cheng; Chen, Ruida; Cai, Zhao; Zhou, Daojin; Hao, Yongchao; Chang, Yingna; Han, Nana; Li, Yaping; Liu, Junfeng; Wang, Feng; Liu, Wen; et al.
Abstract : A hierarchical structure containing aligned CNTs/graphene/transition-metal was fabricated and worked as a highly active bifunctional catalyst for Zn–air batteries. Abstract : The fabrication of cost effective and efficient electrocatalysts with functional building blocks to replace noble metal ones is of great importance for energy related applications yet remains a great challenge. Herein, we report the fabrication of a hierarchical structure containing CNTs/graphene/transition-metal hybrids (h-NCNTs/Gr/TM) with excellent bifunctional oxygen electrocatalytic activity. The synthesis was rationally designed by the growth of shorter nitrogen-doped CNTs (S-NCNTs) on longer NCNTs arrays (L-NCNTs), while graphene layers were in situ generated at their interconnecting sites. The hybrid material shows excellent OER and ORR performance, and was also demonstrated to be a highly active bifunctional catalyst for Zn–air batteries, which could be due to rapid electron transport and full exposure of active sites in the hierarchical structure.